Sarcopenia-related traits and 10 digestive system disorders: insight from genetic correlation and Mendelian randomization - Yang, Tao; Liu, Zheng; Xiu, Mingzhu; Qing, Xiaoman; Liu, Sha; Xiao, Wanmeng; Lü, Muhan (Frontiers in Public Health, 2024)
Introduction Despite observational studies suggest hypotheses indicating a potential link, the precise causal connection between sarcopenia and digestive system illnesses has not been clearly defined. Methods We first use Linkage Disequilibrium Score Regression (LDSC) testing to determine the genetic correlation of traits associated with sarcopenia and 10 specific gastrointestinal diseases. Subsequently, we performed a set of bidirectional Mendelian Randomization (MR) analyses to gauge the genetic inclination towards sarcopenia-related traits in relation to each gastrointestinal condition, individually, across the FinnGen, UK Biobank, and other extensive collaborative consortia. The analytical outcomes were synthesized using a fixed-effects meta-analytic model. For outcomes indicating substantial causal impacts, mediation MR analyses were executed. Additionally, a battery of sensitivity analyses was conducted to evaluate the study’s strength and dependability. Results Our findings established a strong causal link between appendicular lean mass and gastroesophageal reflux disease (OR = 0.8607; 95% CI: 0.8345–0.8877; p < 0.0001) and a noteworthy correlation with nonalcoholic fatty liver disease (OR = 0.7981; 95% CI: 0.7281–0.8749; p < 0.0001), as per the meta-analysis data. We also evaluated the intermediary role of metabolic disorders in the association between appendicular lean mass and the aforementioned diseases. The intermediary effect towards gastroesophageal reflux disease is quantified as 0.0087 (95% CI, 8e-04, 0.0183), accounting for 5.9398% (95% CI, 0.5462, 12.4940%) of the overall effect. For non-alcoholic fatty liver, the intermediary impact is 0.0150 (95% CI, 0.0050, 0.0270), representing 19.7808% (95% CI, 6.5936, 35.6055%) of the total effect. Conclusion The findings posit that augmenting muscle mass may serve as a preventative strategy against gastroesophageal reflux disease and non-alcoholic fatty liver, highlighting the critical role of metabolic disorder management in reducing the risks of these sarcopenia-related conditions.